Changes in the effective connectivity of the social brain when making inferences about close others vs. the self - Esmenio, Sofia (2020)
The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/10.3389/fnhum.2020.00151/full#supplementary-material.